THE SPECIFIC OF TOURIST ACTIVITIES AND PHYSICAL EFFORT ON THE SOUTHERN FACE OF DAMAVAND MOUNTAIN (IRAN, ALBORZ MOUNTAINS) - Ioan BÎCA (Cluj University Press, 2020)
Mount Damavand is part of the 7th Volcano Circuit and is located in the central-southern part of the Alborz Mountains in Iran, 70 km north of Tehran. Due to its altitude of 5610 m, the mountain is a challenge for climbers and imposes a series of atmospheric conditions that induce certain physical stresses during the ascent to the top. The standard route is located on the southern face of the mountain and leaves from the village of Polour to two camps, Goosfand Sara (3000 m) and Bargah Sevom (4200 m). The access to the first camp can be done by car, and from there to the second camp on foot, the luggage being transported by mules by the locals. In the second camp, Bargah Sevom, is a modern stone refuge, which belongs to the Iranian Mountaineering Federation. Sports activities take place in two major stages: acclimatization and climbing to the top, for which at least 2-3 days are allocated. The present study, carried out on the occasion of a scientific, and sports expedition, aims to analyze the organization of tourist activities, the attractive potential and the peculiarities of the effort on the southern face of the mountain, between the altitudes of 3000 m and 5610 m. REZUMAT. Specificul activităților turistice și al efortului fizic pe fața sudică a muntelui Damavand (Iran, Munții Alborz). Muntele Damavand face parte din Circuitul 7 Vulcani și este situat în partea central-sudică a Munților Alborz din Iran, la 70 km nord de orașul Teheran. Prin altitudinea sa de 5610 m, muntele reprezintă o provocare pentru alpiniști și impune o serie de condiții atmosferice care induc anumite solicitări fizice în timpul ascensiunii spre vârf. Traseul standard este situat pe fața sudică a muntelui, și pleacă din localitatea Polour spre două tabere, Goosfand Sara (3000 m) și Bargah Sevom (4200 m). Accesul spre prima tabără se poate face cu mașina, iar de acolo spre tabăra a doua pe jos, bagajele fiind transportate cu catârii de către localnici. În tabăra a doua, Bargah Sevom, se află un refugiu modern din piatră, care aparține Federației Iraniene de Alpinism. Activitățile sportive se desfășoară în două etape mari: aclimatizarea și ascensiunea spre vârf, pentru care se alocă cel puțin 2-3 zile. Studiul de față, efectuat cu ocazia unei expediții științifice și sportive, își propune să analizeze organizarea activităților turistice, potențialul atractiv și particularitățile efortului pe fața sudică a muntelui, între altitudinile de 3000 m și 5610 m. Cuvinte-cheie: circuitul șapte vulcani, muntenărie, agrement montan, frecvență cardiacă, debit cardiac.